Revitalisasi Lingkungan Belajar melalui Fasilitas Visual Edukatif di RA Sekolah Cendekia Berseri - Haedar, Ahmad Wahidiyat; Rizqiyah, Umara Hasmarani; Husnirrahman J; Jusbaeni, Jusbaeni; Muhibuddin, Andi Firman (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Visual-based learning environments play an important role in supporting early childhood education, but their implementation is still not optimal in many schools. This problem was also found in RA Sekolah Cendekia Berseri, Makassar, where visual facilities were not educational enough and did not fully support learning interactions. This Community Partnership Program (PKM) activity aims to improve the quality of the learning environment through revitalizing visual facilities based on a participatory approach. The method used, namely participatory methods including training, diffusion of science and technology, awareness, mentoring, and direct practice involving teachers and students. The activity was carried out on April 11, 2026, involving around 15–20 teachers and education personnel. The results of the study showed a significant increase, marked by the creation of educational murals and a more interactive and child-friendly classroom arrangement. Teachers' understanding of the concept of educational visuals increased from 45% to 85%, spatial planning skills from 50% to 88%, and awareness of the importance of visual media from 55% to 90%. These findings indicate that participatory visual revitalization is effective in improving the quality of the learning environment and teacher capacity. However, limited time and resources remain a challenge, necessitating continued mentoring to ensure the program's sustainability.